Culturally Responsive Literacy Interventions in Speech-Language Pathology: A Scoping Review. - Guiberson, Mark (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose and Method: In this study, the author employed a positivist perspective and framework, utilizing a scoping methodology to systematically explore the extant research literature in speech-language pathology pertaining to literacy interventions for children from culturally and linguistically diverse (CLD) backgrounds. Results: The scoping review encompassed 22 studies selected from a pool of 908 sources, uncovering 34 literacy strategies presented in an evidence map. These strategies, intended for both school-age and preschool children, were implemented across diverse populations, including Indigenous communities, dual language learners, and children with disabilities. The strategies identified offer valuable insights for intervention planning and piloting. Conclusions: The review underscores the significance of culturally responsive literacy interventions in fostering inclusive and supportive learning environments for CLD learners. Additionally, two illustrative case studies are presented to exemplify the application of the identified strategies and discussed in the context of implementing Universal Design for Learning principles for all students.